Efficacy of immunotherapy targeting the neoantigen derived from epidermal growth factor receptor T790M/C797S mutation in non–small cell lung cancer. Issue 8 (18th June 2020) - Akazawa, Yu; Saito, Yuki; Yoshikawa, Toshiaki; Saito, Keigo; Nosaka, Kazuto; Shimomura, Manami; Mizuno, Shoichi; Nakamoto, Yasunari; Nakatsura, Tetsuya
Abstract: Lung cancer is the leading cause of cancer‐related deaths worldwide. Epidermal growth factor receptor‐tyrosine kinase inhibitors (EGFR‐TKI) often have good clinical activity against non–small cell lung cancer (NSCLC) with activating EGFR mutations. Osimertinib, which is a third‐generation EGFR‐TKI, has a clinical effect even on NSCLC harboring the threonine to methionine change at codon 790 of EGFR (EGFR T790M) mutation that causes TKI resistance. However, most NSCLC patients develop acquired resistance to osimertinib within approximately 1 year, and 40% of these patients have the EGFR T790M and cysteine to serine change at codon 797 (C797S) mutations. Therefore, there is an urgent need for the development of novel treatment strategies for NSCLC patients with the EGFR T790M/C797S mutation. In this study, we identified the EGFR T790M/C797S mutation‐derived peptide (790‐799) (MQLMPFGSLL) that binds the human leukocyte antigen (HLA)‐A*02:01, and successfully established EGFR T790M/C797S‐peptide‐specific CTL clones from human PBMC of HLA‐A2 healthy donors. One established CTL clone demonstrated adequate cytotoxicity against T2 cells pulsed with the EGFR T790M/C797S peptide. This CTL clone also had high reactivity against cancer cells that expressed an endogenous EGFR T790M/C797S peptide using an interferon‐γ (IFN‐γ) enzyme‐linked immunospot (ELISPOT) assay. In addition, we demonstrated using a mouse model that EGFR T790M/C797S peptide‐specific CTL were induced by EGFR T790M/C797S peptide vaccine in vivo. These findings suggest that an immunotherapy targeting a neoantigen derived from EGFR T790M/C797S mutation could be a useful novel therapeutic strategy for NSCLC patients with EGFR‐TKI resistance, especially those resistant to osimertinib.